Methadone, Cocaine, Opiates and Metabolite Disposition in Umbilical Cord and Correlations to Maternal Methadone Dose and Neonatal Outcomes - de Castro, Ana (2011)
OBJECTIVES: To explore methadone and 2-ethylidene-1,5-dimethyl-3,3-diphenylpyrrolidine (EDDP) umbilical cord disposition, correlate with maternal methadone dose and neonatal outcomes, and evaluate the window of drug detection in umbilical cord of in utero illicit drug exposure. METHODS: Subjects, 19 opioid-dependent pregnant women from two clinical studies, one comparing methadone and buprenorphine pharmacotherapy for opioid-dependence treatment, and the second examining monetary reinforcement schedules to maintain drug abstinence. Correlations were calculated for methadone and EDDP umbilical cord concentrations and maternal methadone dose, and neonatal outcomes. Cocaine- and opiate-positive umbilical cord concentrations were compared to those in placenta and meconium, and urine specimens collected throughout gestation. RESULTS: Significant positive correlations were found for umbilical cord methadone concentrations and methadone mean daily dose, mean dose during the 3(rd) trimester and methadone cumulative daily dose. Umbilical cord EDDP concentrations and EDDP/methadone concentration ratios were positively correlated to newborn length, peak neonatal abstinence syndrome (NAS) score and time-to-peak NAS score. Methadone concentrations and EDDP/methadone ratios in umbilical cord and placenta were positively correlated. Meconium identified many more cocaine and opiate positive specimens than umbilical cord. CONCLUSION: Umbilical cord methadone concentrations were correlated to methadone doses. Also, our results indicate that methadone and EDDP concentrations might help to predict NAS severity. Meconium proved to be more suitable than umbilical cord to detect in utero exposure to cocaine and opiates; however, umbilical cord could be useful when meconium is unavailable due to in utero or delayed expulsion.